Sterilization of medical waste by electron beam - ZHU Huanzheng; ZHANG Tao; HAN Yunsong; CHEN Hai; HE Shijun (Fushe yanjiu yu fushe gongyi xuebao, 2022)
To study the effectiveness of electron-beam sterilization of medical waste, medical wastes were irradiated with different doses of an electron beam, and Bacillus pumilus and Bacillus atrophaeus were used as microbial indicators.Microbial counting was used to analyze the effects of the absorbed dose and medical waste material on the inactivation of microorganisms. The results showed that the absorbed dose was linearly correlated with the logarithm of the total number of viable microbial colonies; the D10 values of Bacillus pumilus and Bacillus atrophaeus were 2.45 kGy and 1.22 kGy,respectively.When the absorbed dose was 15 kGy, the killing logarithm of Bacillus pumilus and Bacillus atrophaeus on the medical waste simulants reached 6, thereby meeting the current technical requirements for the microwave and chemical disinfection of medical waste.